(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The essence and main characteristics of electronic attack (EA) are examined, as well as its place in the electronic warfare (EW). The main elements of EA are examined, such as jamming, spoofing and electronic neutralization of enemy radio devices. A definition and the main terms for software-defined radio (SDR) are given. The architecture and main characteristics of SDR are examined. A prototype of SDR is made and demonstrated for the purpose of proving the concept.